Genetically predicted causal link between the plasma lipidome and pancreatic diseases: a bidirectional Mendelian randomization study - Lin, Liaoyi; Huang, Yingbao; Qian, Songzan; Chen, Lifang; Sun, Houzhang (Frontiers in Nutrition, 2025)
BackgroundRecent studies have increasingly emphasized the strong correlation between the lipidome and the risk of pancreatic diseases. To determine causality, a Mendelian randomization (MR) analysis was performed to identify connections between the lipidome and pancreatic diseases.MethodsStatistics from a genome-wide association study of the plasma lipidome, which included a diverse array of 179 lipid species, were obtained from the GeneRISK cohort study with 7,174 participants. Genetic associations with four types of pancreatitis and pancreatic cancer were sourced from the R11 release of the FinnGen consortium. Two pancreatitis datasets from UK Biobank were employed as the validation cohort. MR analysis was conducted to assess the relationship between the genetically predicted plasma lipidome and these pancreatic diseases. Inverse variance weighted was adopted as the main statistical method. Bayesian weighted MR was employed for further verification. The MR-Egger intercept test for pleiotropy and Cochrane's Q statistics test for heterogeneity were performed to ensure the robustness.ResultsMR analysis yielded significant evidence that 26, 25, 2, and 19 lipid species were correlated with diverse outcomes of pancreatitis, and 8 lipid species were correlated with pancreatic cancer. Notably, sterol ester (27:1/20:2) levels (OR: 0.84, 95% CI: 0.78–0.90, P = 5.79 × 10−7) were significantly associated with acute pancreatitis, and phosphatidylcholine (17:0_20:4) levels (OR: 0.89, 95% CI: 0.84–0.94, P = 1.78 × 10−4) and sterol ester (27:1/20:4) levels (OR: 0.90, 95% CI: 0.86–0.95, P = 2.71 × 10−4) levels were significantly associated with chronic pancreatitis after the Bonferroni-corrected test. As for validation, 14 and 9 lipid species were correlated with acute and chronic pancreatitis of UK Biobank. Some lipid classes showed significant effects both in the FinnGen consortium and UK Biobank datasets.ConclusionsThe findings of this study indicate a potential genetic predisposition linking the plasma lipidome to pancreatic diseases and good prospects for future pancreatic disease clinical trials.